Low levels of vitamin D are common in primary antiphospholipid syndrome with thrombotic disease - P.L. Meroni; F. Allegri; L. Andreoli; S. Piantoni; A. Tincani (PAGEPress Publications, 2012)
The aim of this study was to assess vitamin D (vit.D) levels in patients with primary antiphospholipid syndrome (PAPS), the association between hypovitaminosis D and clinical manifestations, and the effect of vit.D supplementation on serum levels. Vit.D serum levels of 115 PAPS patients, classified according to the 2006 revised criteria at the Rheumatology Department, Brescia, and of 128 voluntary healthy donors (NHD) were tested in collaboration with DiaSorin (Saluggia, Italy) using the LIAISON® chemiluminescent immunoassay. Clinical data were derived from clinical charts. Vit.D deficiency was more prevalent in PAPS than NHD (17% vs 5%). During the summer, vit.D levels were lower in PAPS than NHD (median 28 vs 40.1 ng/mL, P<0.01). PAPS were subdivided according to clinical characteristics (thrombotic vs obstetric). Both groups had lower vit.D levels compared to NHD. Thrombotic PAPS had significantly lower levels than obstetric PAPS (median 20.8 vs 33.3, P<0.01). Sixteen patients (14%) received oral 25-OH vit.D supplementation (average 400 UI/die), but 63% of them did not reach serum levels above 30 ng/mL. PAPS showed significantly lower levels of vit.D than NHD. Hypovitaminosis D was seen to cluster in patients with thrombosis which may suggest that the lack of vit.D could be one of the many factors involved in the thrombotic process. Low-dose supplementation did not seem to be effective in a small group of patients.